Radiographic Comparison of Mandibular Third Molar Mesioangulation in Orthodontic Treatment : Assessing the Impact of First Premolar Extraction Versus Non-Extraction Strategies - Almazuhra Adisty Siregar; Athica Putri Basyari; Yunita Savitri; Alhidayati Asymal; Nastiti Faradilla Ramadani (International Journal of Health and Medicine, 2025)
The angulation of third molars plays a crucial role in dental health and orthodontic outcomes. This review examines changes in third molar mesioangulation after orthodontic treatment, comparing cases involving first premolar extractions with non-extraction protocols. Research has shown that premolar extractions often result in significant improvements in third molar angulation, promoting easier eruption and reducing the likelihood of impactions. Conversely, non-extraction cases generally demonstrate less favorable changes, with a higher frequency of impactions and limited spontaneous correction of molar positioning. The extent and direction of these changes depend on individual factors such as the degree of crowding and the developmental stage of the third molars at the start of treatment. Premolar extraction during orthodontic procedures appears to enhance third molar angulation, potentially lowering the risk of impaction and reducing the need for surgical removal. However, some studies highlight the influence of individual anatomical variations, suggesting that premolar extraction does not consistently produce uniform angulation changes in all patients. Therefore, orthodontic treatment planning should weigh the potential advantages of premolar extractions in improving third molar alignment, especially for patients with a higher risk of molar impaction